Root-knot nematodes associated with beans in Colombia and Peru and related yield loss - Mullin, BA; Abawi, G.S.; Pastor Corrales, Marcial A.; Kornegay, Julia L. (Scientific Societies, 1991)
A survey of root-knot nematodes associated with bean (Phaseolus vulgaris) roots and soils in the major bean production regions of Colombia and Peru was conducted during 1988 1989. Over 150 samples were processed for these parasites, and specimens from more than 100 of the collections were identified to species. Samples were collected from departments of Valle, Cauca, Nariño, Antioquia, and Tolima of Colombia and from Ica, Lima, Ancash, La Libertad, and Cajamarca of Peru. Only Meloidogyne incognita and M. javanica were detected in Peru, at frequencies of 66 and 7%, respectively, of the samples collected. In Colombia, M. incognita, M. javanica, M. hapla, and M. arenaria were detected at frequencies of 62, 21, 14, and 14%, respectively. Mixtures of root-knot species were common in samples from Colombia but rare in samples from Peru. Yield loss due to root-knot nematodes (M. incognita and M. javanica) was assessed by a field-infestation technique, and comparable plots of the commercial bean cultivar Calima and the CIAT advanced bean line PVA 916 were planted in infested plots and in uninfested plots 15 m from the infested ones. The nematodes induced yield losses of 45 63% to Calima and 26 32% to PVA 916, as determined by dry seed weight. Yield loss due to nematodes was greater with concurrent leafhopper (Empoasca kraemeri) damage.